Creatine affords protection against glutamate-induced nitrosative and oxidative stress. (May 2016) - Cunha, Mauricio P.; Lieberknecht, Vicente; Ramos-Hryb, Ana Belén; Olescowicz, Gislaine; Ludka, Fabiana K.; Tasca, Carla I.; Gabilan, Nelson H.; Rodrigues, Ana Lúcia S.
Abstract: Creatine has been reported to exert beneficial effects in several neurodegenerative diseases in which glutamatergic excitotoxicity and oxidative stress play an etiological role. The purpose of this study was to investigate the protective effects of creatine, as compared to the N-Methyl-d -Aspartate (NMDA) receptor antagonist dizocilpine (MK-801), against glutamate or hydrogen peroxide (H2 O2 )-induced injury in human neuroblastoma SH-SY5Y cells. Exposure of cells to glutamate (60–80 mM) or H2 O2 (200–300 μM) for 24 h decreased cellular viability and increased dichlorofluorescein (DCF) fluorescence (indicative of increased reactive oxygen species, ROS) and nitric oxide (NO) production (assessed by mono-nitrogen oxides, NOx, levels). Creatine (1–10 mM) or MK-801 (0.1–10 μM) reduced glutamate- and H2 O2 -induced toxicity. The protective effect of creatine against glutamate-induced toxicity involves its antioxidant effect, since creatine, similar to MK-801, prevented the increase on DCF fluorescence induced by glutamate or H2 O2 . Furthermore, creatine or MK-801 blocked glutamate- and H2 O2 -induced increases in NOx levels. In another set of experiments, the repeated, but not acute, administration of creatine (300 mg/kg, po ) in mice prevented the decreases on cellular viability and mitochondrial membrane potential (assessed by tetramethylrhodamine ethyl ester, TMRE, probe) of hippocampal slices incubated with glutamate (10 mM). Creatine concentration-dependent decreased the amount of nitrite formed in the reaction of oxygen with NO produced from sodium nitroprusside solution, suggesting that its protective effect against glutamate or H2 O2 -induced toxicity might be due to its scavenger activity. Overall, the results suggest that creatine may be useful as adjuvant therapy for neurodegenerative disease treatments. Highlights: Creatine affords protective effect against glutamate and H2 O2 toxicity in SH-SY5Y cells. The antiexcitotoxic property of creatine involves its antioxidant effect. Creatine prevented ROS production induced by glutamate and H2 O2 . Creatine blocked glutamate- and H2 O2 -induced increases in NOx levels. Creatine decreased nitrite levels formed from solution of sodium nitroprusside.